Role of meningeal lymphatic vessels in brain homeostasis - Zhao, Meng-Ying; Ye, Chao-Yuan; Liu, Yuan-Cheng; Wang, Xiao-Ming; Fu, Jun-Cai; Liu, Xin-Yuan; Zhu, Rui; Li, Yi-Zhao; Tian, Qing (Frontiers in Immunology, 2025)
Meningeal lymphatic vessels (MLVs) form an important bridging structure between the brain and periphery, which drains cerebral metabolites in cerebrospinal fluid (CSF) and brain antigens to deep cervical lymph nodes (dCLNs), to maintain brain homeostasis. Increasing evidence reveals the importance of MLVs in brain ageing and various central nervous system (CNS) diseases, such as Alzheimer’s disease (AD), Parkinson’s disease (PD), traumatic brain injury (TBI), and multiple sclerosis (MS). Advances in research techniques have provided detailed insights into the structure and functions of MLVs, highlighting the therapeutic potential of targeting MLVs for related diseases. Here, we perform a systematic review of the features and functional regulation of MLVs, their associations with brain disorders, as well as some methodological advances in imaging of MLVs and the drainage pathway.